The Political Economy of Tax Incentives for Investment in the Dominican Republic "Doctoring the Ball - Daude, Christian (OECD Publishing, 2014)
Tax incentives can be a useful tool to stimulate investment in developing countries. However, in these countries interest groups often are able to exert considerable influence in its management, if not its design. From a power-based approach to the political economy of tax reform we find how interest groups work within the institutional framework to seek outcomes that best fit their objectives. When unsuccessful, they become powerful advocates of change. These power dynamics have important implications for the design and management of tax incentives in developing economies
Keywords: Development; Dominican Republic